Potamopyrgus antipodarum in Central Portugal and Madeira Island: abundance and impacts on the structure of benthic communities - Dias, Marcos Rodrigues Rocha (2022)
Biotic invasions are a significant component of human-caused global environmental change. Alien invasive species reveals to be the main driving force behind species extinctions and a major threat to ecosystem services, diversity and genetic diversity of native species. Potamopyrgus antipodarum (Gray, 1843) is a parthenogenic freshwater hydrobiid snail native to New Zealand. It has been considered as one of the most successful and widespread invasive freshwater mollusks worldwide. Although P. antipodarum can dominate macroinvertebrate communities in Europe, in Iberian Peninsula only a weak effect on macroinvertebrate communities has been reported so far. The aim of this work was to evaluate the presence and the densities of P. antipodarum in lotic systems in Central Portugal and Madeira Island, and to know if and how the presence of this snail affects the native macroinvertebrate communities. To achieve those goals, 20 locations of 13 streams were sampled in Madeira Island and Central Portugal (Mondego and Vouga tributaries), with semiquantitative kick and sweep (K&S) and quantitative Surber net (SN) macroinvertebrates sampling techniques. The benthic communities were identified on the laboratory, and P. antipodarum densities and the composition and abundance of the communities were accessed. P. antipodarum was found in all locations of Central Portugal and densities ranged from 10 to 908 ind./m² (mean values), and it was found in nearly all locations of Madeira Island and abundances ranged from 3 to 3528 organisms. In Central Portugal, the composition and structure of native macroinvertebrate communities was negatively affected by high densities of P. antipodarum. Relatively high densities of P. antipodarum were associated with i) a decrease in species richness, diversity and evenness; ii) an increase in one species domination; iii) a decrease in sensitive species (Ephemeroptera, Plecoptera and Trichoptera); iv) and with a decrease in native shredders and scrapers/grazers species. In Madeira Island, the first record of the species' presence on the island was found, supporting the evidence that the species arrived at Madeira Island in the last years, and it is now in the spreading phase. However, macroinvertebrate community analyzes do not yet indicate a clear impact on macroinvertebrate community structure. This study contributes with new information on the presence of P.antipodarum in Central Portugal and Madeira Island, and provides a first attempt to understand their impacts on natural macroinvertebrate communities. This first approach reinforces the need for more detailed studies to find new evidence of the invasive role of P.antipodarum in stream of Portugal an d to find more consequences to aquatic communities and ecosystems, for a better understanding of P.antipodarum invasion in Mediterranean ecosystems and propose better management plans.